2019
DOI: 10.1111/gwat.12966
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Storage Change in the Jinsha River Basin from GRACE, Hydrologic Models, and In Situ Data

Abstract: Groundwater plays a major role in the hydrological processes driven by climate change and human activities, particularly in upper mountainous basins. The Jinsha River Basin (JRB) is the uppermost region of the Yangtze River and the largest hydropower production region in China. With the construction of artificial cascade reservoirs increasing in this region, the annual and seasonal flows are changing and affecting the water cycles. Here, we first infer the groundwater storage changes (GWSC), accounting for sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…Soil moisture in‐situ observation networks were constructed to validate satellite retrievals and improve the modeling of soil moisture (Dente et al., 2012; Su et al., 2011; Yang et al., 2013). Previous studies found an increasing GWS in the subregions of the TP from the early 2000s (Bibi et al., 2019; Chao et al., 2019; Jiao et al., 2015; Xiang et al., 2016; Zhang et al., 2017) and attributed the GWS changes to various factors including precipitation, evapotranspiration, glacier retreat, permafrost degradation, snow melt, ecological project, etc. However, the dominant factors controlling the long‐term changes in GWS remain unclear and its response to climate change is not well understood, thereby calling for improved estimations of the water storage components and a holistic analysis of GWS changes as well as their driving factors.…”
Section: Introductionmentioning
confidence: 97%
“…Soil moisture in‐situ observation networks were constructed to validate satellite retrievals and improve the modeling of soil moisture (Dente et al., 2012; Su et al., 2011; Yang et al., 2013). Previous studies found an increasing GWS in the subregions of the TP from the early 2000s (Bibi et al., 2019; Chao et al., 2019; Jiao et al., 2015; Xiang et al., 2016; Zhang et al., 2017) and attributed the GWS changes to various factors including precipitation, evapotranspiration, glacier retreat, permafrost degradation, snow melt, ecological project, etc. However, the dominant factors controlling the long‐term changes in GWS remain unclear and its response to climate change is not well understood, thereby calling for improved estimations of the water storage components and a holistic analysis of GWS changes as well as their driving factors.…”
Section: Introductionmentioning
confidence: 97%
“…So far, the groundwater change has been investigated via removing other components from TWS using LSM models [35,36,[65][66][67][68][69] or integrated with geographic information system [70]. This is because of the lack of the groundwater measurements.…”
Section: Analysis Of Tws Anomalous Change In 2006mentioning
confidence: 99%
“…Though using different models, Bibi et al [71] also revealed a sharp increase of groundwater in Qiadam Basin in the second half of 2006. Besides the rising temperature, water seepage and other natural causes, Chao et al [36] suggests that the groundwater change in this region is also influenced by human activities, such as dam construction. Overall, the origin of TWSA anomaly in 2006 can be arisen in two aspects.…”
Section: Analysis Of Tws Anomalous Change In 2006mentioning
confidence: 99%
“…There are many methods used for modeling and detecting groundwater, one of which is gravity anomaly [10]. Currently, the anomaly gravity approach from satellite data has not been applied for modeling groundwater and drought potential in Indonesia.…”
Section: Introductionmentioning
confidence: 99%